Radiation-induced alterations in histone modification patterns and their potential impact on short-term radiation effects - Friedl, Anna A.; Mazurek, Belinda; Seiler, Doris M. (Frontiers in Oncology, 2012)
Detection and repair of radiation-induced DNA damage occur in the context of chromatin. An intricate network of mechanisms defines chromatin structure, including DNA methylation, incorporation of histone variants, histone modifications, and chromatin remodelling. In the last years it became clear that the cellular response to radiation-induced DNA damage involves all of these mechanisms. Here we focus on the current knowledge on radiation-induced alterations in post-translational histone modification patterns and their effect on the chromatin accessibility, transcriptional regulation and chromosomal stability.